A Case of Retroperitoneal Castleman's Disease and an Update on the Latest Evidence. (5th November 2014) - Spartalis, Eleftherios; Charalampoudis, Petros; Kandilis, Apostolos; Athanasiou, Antonios; Tsaparas, Petros; Voutsarakis, Athanasios; Kostakis, Ioannis D.; Dimitroulis, Dimitrios; Svolou, Evanthia; Korkolopoulou, Penelope; Nikiteas, Nikolaos; Kouraklis, Gregory
Abstract : Castleman's disease is a benign lymphoproliferative condition with three distinct histological subtypes. Clinically it presents in either a unicentric or multicentric manner and can affect various anatomic regions, the mediastinum being the most frequent location. We herein present a rare case of unifocal retroperitoneal mass proved to be hyaline vascular Castleman's disease. We perform a review of the current literature pertaining to such lesions, focusing on the management of the various clinical and histological variants of the disease. Surgical excision is the treatment of choice for unifocal Castleman's disease.